Pengetahuan Masyarakat Suku Tengger Terhadap Jenis Tumbuhan Liar Sebagai Bahan Bertahan Hidup Di Hutan Kawasan TNBTS, Kabupaten Malang Provinsi Jawa Timur - M. Eval Setiawan; Suhadi; Sri Endah Indriwati (Fakultas Tarbiyah dan Ilmu Keguruan, Institut Agama Islam Negeri Kerinci, 2020)
Using the wild plant for consumptino is a knowledge passed down through generations that can be documented for the purposes of futher study. This study aim to document the kind of wlind plant for survival in TNBTS . the method used is descriptive analisis with data collection techniques throuhg in-depth interviews and continued exploration of plants along the route of ascent of mount semeru. Base on the result of in-depth interviews and exploration of found 9 spesiesof plants that can be uses to survival material in TNBTS. Parts of the plants used is the leave. Plants in can be found alonge side the route of travel, the edge of the forets anf in the forest